Substitutability of natural and human capitals: lessons from a simple exploratory model - Jesse T. Rieb; Brian E. Robinson; Elena M. Bennett (Ecosystems and People, 2023)
ABSTRACTMost ecosystem services (ES) are co-produced, to varying degrees, by interactions between people and ecosystems. Although ES research has tended to emphasize the role of ecosystems, or natural capital, in ES provision, the need for a deeper understanding of the role of human-derived capitals, like technology, labour, and management, is increasingly being recognized. Understanding the capacity for, and limitations of, human-derived capitals to enhance or substitute for natural capital is important for environmental decision-making, especially for decisions about when to promote conservation of natural capital to provide ecosystem services and when to employ technological alternatives. From the perspective of long-term sustainable ecosystem management, such decisions are further complicated by dynamics and interactions between different types of capital. We created a simple simulation model to compare how different assumptions around the temporal dynamics and interactions between natural and human-derived capitals affect long-term outcomes of different management choices on ES provision. We found that the extent to which different capitals are substitutable in the long-term depends on how individual capitals change over time and how different capitals interact with each other, and that replicating the near-term function of natural capital does not necessarily mean human-derived capitals are a viable long-term substitute. With an understanding of the dynamics and interactions of natural and human-derived capitals, it is possible to determine general long-term ES management strategies that are more likely to produce the desired benefits.